The QuantiFERON Monitor® assay is predictive of infection post allogeneic hematopoietic cell transplantation. Issue 3 (29th February 2020) - Douglas, Abby P.; Yu, Lijia; Sundararajan, Vijaya; Szer, Jeff; Ritchie, David; Slavin, Monica A; Sasadeusz, Joe; Visvanathan, Kumar
Abstract: Introduction: Following allogeneic hematopoietic stem cell transplantation (alloHCT), excessive immunosuppression can be complicated by infection, while inadequate immunosuppression can result in graft‐vs‐host disease (GVHD). An accurate method to assess overall immune status post HCT is lacking. The QuantiFERON Monitor ® (QFM) assay measures interferon gamma (IFN‐γ) release from whole blood following incubation with both innate (Toll‐like receptor 7, TLR7) and adaptive (CD3 antibody) stimulants and may result in a more complete assessment of the immune system. Methods: Whole blood samples were prospectively collected from alloHCT recipients at conditioning followed by days 10, 30, 60, 90, 120, and 180 post‐transplant and assayed by the QFM test. IFN‐γ levels were correlated to time post HCT and episodes of infection and GVHD. Results: Forty patients were enrolled in the study (68% male; median age 47 years; 58% matched related donors, 42% unrelated; 33% myeloablative). Post‐stimulation IFN‐γ levels rose steadily over the first 180 days post transplantation. IFN‐γ levels were significantly lower in those with active infection compared to those without during the neutropenic period ( P  < .001). The assay was predictive of CMV reactivation (VL > 1000 copies/mL) post alloHCT ( P  = .001). Conclusion: This is a promising assay to demonstrate immune recovery and predict risk of infection after alloHCT and may allow tailoring of immunosuppression, antimicrobial treatment, and prophylaxis.